2005
DOI: 10.1002/pmic.200401309
|View full text |Cite
|
Sign up to set email alerts
|

Heat-shock protein 27: A potential biomarker for hepatocellular carcinoma identified by serum proteome analysis

Abstract: Hepatocellular carcinoma (HCC) is the third leading cause of cancer mortality worldwide and ranks second in China. The prognosis of HCC remains dismal mainly because of its late diagnosis, especially in patients with coexisting chronic liver diseases. To identify serum biomarkers for HCC, sera from 20 healthy volunteers, 20 hepatitis B virus (HBV) infected patients and 20 HCC patients were selected for screening study and same number of sera into the same three groups were used for validation study. A strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
124
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(133 citation statements)
references
References 34 publications
7
124
1
1
Order By: Relevance
“…Similar to previous reports (12,13), our study clearly shows the identified set of differentially overexpressed proteins, including serum amyloid A protein (SAA1), HP and sp40, between LC and HCC patients by 2-DE. They are all members of acute phase proteins (APPs) family, and most were responsible for liver-synthesized proteins.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similar to previous reports (12,13), our study clearly shows the identified set of differentially overexpressed proteins, including serum amyloid A protein (SAA1), HP and sp40, between LC and HCC patients by 2-DE. They are all members of acute phase proteins (APPs) family, and most were responsible for liver-synthesized proteins.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, by comparing these results with the most relevant study (12), the alteration of haptoglobin coincided with the previous studies. In our study, in conjunction with Western blot results and measurement of serum haptoglobin, we found that serum HP concentrations were increased in patients with HCC.…”
Section: Discussionsupporting
confidence: 65%
“…Several new HCC tumor markers have recently been clinically evaluated and found to be useful in HCC diagnosis, especially AFP-L3 and DCP [29,[32][33][34][35][36] as well as possibly hsp27, osteopontin, and glypican 3 [37][38][39][40][41]. The rapidly evolving fields of genomics and proteomics are now finding HCC-associated gene products that will likely find future usefulness in further defining HCC prognostic subsets [42][43][44], including metastasis potential [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as described previously (9). Briefly, the protein concentrations was firstly measured using the Bradford assay, and 20 µg protein/lane was resolved on 12.5% SDS-PAGE.…”
Section: In-gel Tryptic Digestion and Maldi-tof Msmentioning
confidence: 99%
“…The silver stained gels were scanned, and resulting images were analyzed using the ImageMaster™ 2D Platinum Software (Version 5.0, Amersham Bioscience, Swiss Institute of Bioinformatics, Geneva, Switzerland) for spot detection, quantification, as well as comparative analyses, as described previously (9). Triplicates of 2-DE gels from each sample were produced to minimize run-to-run variation.…”
Section: Removal Of High Abundance Proteins From Serum Samplesmentioning
confidence: 99%